Plague, Quarantines and Geopolitics in the Ottoman Empire - Bulmus, Birsen (Edinburgh University Press, 2005)
Did you know that many of the greatest and most colourful Ottoman statesmen and literary figures from the 15th to the early 20th century considered plague as a grave threat to their empire? And did you know that many Ottomans applauded the establishment of a quarantine against the disease in 1838 as a tool to resist British and French political and commercial penetration? Or that later Ottoman sanitation effort to prevent urban outbreaks would help engender the Arab revolt against the empire in 1916? Birsen Bulmus explores these facts in an engaging study of Ottoman plague treatise writers throughout their almost 600-year struggle with this epidemic disease. Along the way, she addresses the political, economic and social consequences of the methods they used to combat it.